Analisis Pengaruh Modal, Umur, Jam Kerja, Pengalaman Kerja, Dan Pedidikan Terhadap Pendapatan Nelayan Di Kedonganan - Syadona Putra, Putu Mahendra; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
Indonesia has a vast ocean area that causes sea products in Indonesia is very potential, so many residents livelihood as fishermen. Bali is one of the provinces that has a potential marine wealth, one of the areas in Bali which has a potential marine resources is Kedonganan Village. This research data is obtained from structured interview using questionnaire. The number of samples of the techniques taken in this study is 73 fishermen, while the sampling method is by random sampling technique. Analytical technique used in this research is multiple linear analysis that is to know how big influence of independent variable to dependent variable. Simultaneously, the variable of capital, age, working hours, work experience , and education have positive and significant influence to income  fishermen in Kedonganan Village, Bali. By partial variable of capital, working hours, work experience, and education  have positive and significant influence to income fisherman in Kedonganan village, Bali, while age variable have negative effect no significant significant effect on income fishermen in the village of Kedonganan, Bali